Antioxidant Activity of Phyllanthus niruri Extract, Rutin and Quercetin - Djaja Rusmana; Roro Wahyudianingsih; Mariska Elisabeth; Balqis Balqis; Maesaroh Maesaroh; Wahyu Widowati (The Indonesian Biomedical Journal, 2017)
BACKGROUND: Normal metabolism of oxygen and exogenous factors constantly generate free radicals which could be harmful to the human body. Human need antioxidants to provide protection against free radicals, thus plants are a good source of natural antioxidants. Phyllanthus niruri (P. niruri) has been known to possess several medicinal properties and contain numerous active phytochemical. In this research, we conducted phytochemical screening and antioxidant assay of P. niruri extract along with the compounds rutin and quercetin, which are flavonoids possessing medicinal properties. This study was conducted to determine P. niruri, rutin and quercetin as antioxidant.METHODS: In this study, qualitative phytochemical screening was performed to detect phenol, flavonoid, saponin, tannin, steroid/triterpenoid, terpenoid and alkaloid in P. niruri extract. Antioxidant analysis of P. niruri, rutin and quercetin was conducted using total measured phenolic content, 2,2-diphenyl-1-picrylhydrazil (DPPH), 2,2’-azinobis-3-ethylbenzo-thiazoline-6-sulfonic acid (ABTS) and ferric reducing antioxidant power (FRAP) assays.RESULTS:  The study revealed that P. niruri extract contained saponin, phenol, flavonoid and tannin based on phytochemical screening. In DPPH and ABTS assays quercetin possessed highest antioxidant activity with IC50 value of 0.55 and 1.17 μg/ml respectively. Meanwhile, P. niruri extract showed the highest FRAP activity which was 373.95 μM Fe(II)/μg extract. Rutin possessed the lowest antioxidant activity in all antioxidant assays.CONCLUSION: This study confirmed that P. niruri extract and quercetin have great potential as a natural antioxidant source.KEYWORDS: asntioxidant, phytochemical, Phyllanthus niruri, quercetin, rutin, free radical